Analysis of the Effectiveness of Budget Management in 2021 at the Secretariat of the Bali Provincial DPRD - Ni Made Diah Karisma Rustanti; Kadek Januarsa Adi Sudharma (Sosio e-Kons, 2022)
The existence of a community paradigm that demands the realization of Good Governance requires every apparatus to provide systematic, transparent and accountable financial management information, so that government budgets managed by regional apparatus in the public sector must apply effective principles that make assessment indicators in financial performance. The government's performance appraisal is influenced by the effectiveness factor in budget management, so that the performance of a government agency will be assessed as good if the government is able to achieve the level of spending effectiveness so that the budget can achieve its goals without a budget deficit. The purpose of this study is to determine the level of effectiveness of budget management in 2021 at the Bali Provincial DPRD Secretariat. The analytical method used in the implementation of this research is descriptive quantitative. The data collection technique was carried out through documentation which referred to the search for data on the realization of the budget realization of the Provincial DPRD Secretariat in Bali for the year and used the measurement of the effectiveness ratio as a data analysis technique. The results showed that the effectiveness of the budget management of the Bali Provincial DPRD Secretariat in 2021 reached 76% in the Less Effective category. However, despite a decrease in the level of effectiveness in budget management in 2021, all targets planned at the Bali Provincial DPRD Secretariat have been well implemented and realized.